STABILITAS, HAMBATAN DAN OLAH GERAK KAPAL IKAN MULTI PURPOSE NET/LINE HAULER 20 GT BERDASARKAN KAJIAN UKURAN DAN BENTUK KASKO KAPAL - Arif Fadillah; Shanty Manullang; Rizky Irvana (Bogor Agricultural University, 2019)
Fishing boats are used in capturing or collecting aquatic resources. As a means of production, the boat should meet various conditions of seaworthiness i.e. good stability, good seakeeping ability and minimum resistance. Those criteria can be identified when the boat size and the hull form are designed. This study investigates the effect of the boat dimension and the hull form on the stability, resistance and seekeeping ability. Various sizes and hull shapes of a 20 GT fishing boat were simulated, and their performances were compared to the IMO standard. The results suggest that the minimum breadth (B) - draft (d) ratio which meets the stability criterion is 2.50, while the ratio of the center of gravity distance from the keel (KG) and the depth (D) of the boat is 0.65. Furthermore, for the boat with a higher B and D ratio, its resistance is relatively smaller. In terms of seakeeping ability, particularly roll and pitch motions, U type bottom performed better than the Akatsuki bottom. Keywords: fishing vessel, sea keeping, ship hull, stability, resistance